Advanced age is not a barrier to creating a functional arteriovenous fistula: a retrospective study. Issue 4 (July 2017) - Beaulieu, Monica C.; Dumaine, Chance S.; Romann, Alexandra; Kiaii, Mercedeh
Introduction: Arteriovenous fistulas (AVFs) are the recommended form of vascular access for hemodialysis. However, controversy exists regarding whether AVFs are suitable for elderly patients. Methods: Single-center retrospective review to investigate the impact of age on AVF outcomes. Five hundred and twenty-five patients with AVF creation were stratified based on age <65, 65-75, and >75 years. AVF outcomes including primary failure, AVF patency (primary, secondary, and functional), and AVF complications were studied for 3 years following AVF creation. Results: The cohort was 63% male, 44% Caucasian, and 55% had diabetes or cardiovascular disease. 39% were aged <65 years, 33% 65-75 years, and 28% were aged >75 years. No differences in rates of primary failure, loss of primary patency, complications, or need for intervention were observed between age groups. There was a significant association of age with secondary patency and functional patency, with age >75 being an independent risk factor for shortened lifespan of the fistula. For patients aged >75 years, secondary patency at 3 years was 64% compared to 75%-78% for younger patients. Functional patency at 2 years was 69% for those aged >75 years compared to 78%-81% for younger patients. Conclusions: We found no difference in AVF maturation, primary patency, complications, or interventions in those over the age of 75 compared to younger counterparts. While secondary and functional patency rates were significantly lower in those aged >75 years, the magnitude of difference is likely not clinically relevant. Therefore, we recommend that advanced age alone should not preclude patients from AVF creation.